Optimasi Penjadwalan dan Percepatan Proyek Upgrade H2S Analyzer dengan Metode CPM dan PERT - Al Veronica, Uzi; Sutrisno, Sutrisno; Anugrah, Siti Nabilah Putri; Anisti, Tiara Nanda; Wildan Fatchan Maulidin (Fakultas Teknik Universitas Tulang Bawang, 2025)
Project delays are a major threat in project management that can result in increased costs and decreased operational efficiency. Therefore, an appropriate planning method is needed to optimize the schedule and reduce the risk of delays. This study aims to analyze the critical path and determine the optimal time in the H₂S Analyzer Upgrade project using the Critical Path Method (CPM) and Program Evaluation and Review Technique (PERT). CPM is used to identify critical activities, namely contracts (A), field surveys (B), specifications (C), H₂S Analyzer (F), tubing & tubing connections (G), sample conditioning systems (H), accessories (I), electrical & instrument cables (J), bulk materials (K), and spare parts for one year of operation (L). The results of the analysis show that the CPM method estimates the project duration of 235 days. Meanwhile, the PERT method provides an estimate of completion in the range of 221 to 251 days, with a probability of project success being completed in 221 days of 0.14%, and in 251 days of 99.86%. The implementation of this method improves the accuracy of project scheduling and supports efficiency in resource management. The results of this study recommend combining CPM and PERT with other optimization techniques, such as crashing, to improve project time and cost efficiency. Keywords: CPM, Critical Path, PERT, Project Management, Time Optimization